The shape of things to come: importance of design in nanotechnology for drug delivery. (February 2012) - Liu, Yaling; Tan, Jifu; Thomas, Antony; Ou-Yang, Daniel; Muzykantov, Vladimir R
The design of nanoparticle (NP) size, shape and surface chemistry has a significant impact on their performance. While the influences of the particle size and surface chemistry on drug delivery have been studied extensively, little is known about the effect of particle shapes on nanomedicine. In this perspective article, we discuss recent progress on the design and fabrication of NPs of various shapes and their unique delivery properties. The shapes of these drug carriers play an important role in therapeutic delivery processes, such as particle adhesion, distribution and cell internalization. We envision that stimuli-responsive NPs, which actively change their shapes and other properties, might pave way to the next generation of nanomedicine.